Effects of discharge, wind, and tide on sedimentation in a recently restored tidal freshwater wetland. Issue 16 (28th June 2017) - Verschelling, Eelco; van der Deijl, Eveline; van der Perk, Marcel; Sloff, Kees; Middelkoop, Hans
Abstract: Sediment deposition is one of the key mechanisms to counteract the impact of sea level rise in tidal freshwater wetlands (TFWs). However, information about sediment deposition rates in TFWs is limited, especially for those located in the transition zone between the fluvially dominated and tidally dominated sections of a river delta where sedimentation rates are affected by the combined impact of river discharge, wind, and tides. Using a combined hydrodynamic–morphological model, we examined how hydrometeorological boundary conditions control sedimentation rates and patterns in a TFW located in the Rhine–Meuse estuary in the Netherlands. The modelling results show that net sedimentation rate increases with the magnitude of the river discharge, whereas stronger wind increasingly prevents sedimentation. Sediment trapping efficiency decreases for both increasing river discharge and wind magnitude. The impact of wind storms on the trapping efficiency becomes smaller for higher water discharge. The spatial sedimentation patterns are affected by all controls. Our study illustrates the importance of evaluating both the separate and the joint impact of discharge, wind, and tides when estimating sedimentation rates in a TFW affected by these controls. Such insights are relevant to design measures to reactivate the sedimentation process in these areas.